2022
DOI: 10.3168/jds.2021-21491
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of Wisconsin and California scoring systems to detect bovine respiratory disease in preweaning dairy calves under subtropical environmental conditions

Abstract: Bovine respiratory disease (BRD) is a multifactorial disease which causes short-and long-term negative effects. Early detection is crucial for a prompt response to therapy, as well as to decrease mortality risk. Clinical scoring systems have been developed mostly in North America for screening calves at risk or suspected of having BRD, and these tools have also been applied in subtropical and tropical countries. However, it has been unknown whether these scoring systems had the same accuracy in tropical enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…The use of thoracic ultrasonography is considered accurate to detect respiratory diseases in bovine [ 58 ]. Studies comparing the efficiency of many clinical signs and clinical score systems to thoracic ultrasonography for diagnosing respiratory diseases were published [ 59 , 60 ]. Lowie et al [ 60 ] found that spontaneous cough was the clinical sign that best indicated a calf to have respiratory diseases; however, the performance of this clinical sign is relatively poor (Se = 37.4%, Sp = 85.7%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of thoracic ultrasonography is considered accurate to detect respiratory diseases in bovine [ 58 ]. Studies comparing the efficiency of many clinical signs and clinical score systems to thoracic ultrasonography for diagnosing respiratory diseases were published [ 59 , 60 ]. Lowie et al [ 60 ] found that spontaneous cough was the clinical sign that best indicated a calf to have respiratory diseases; however, the performance of this clinical sign is relatively poor (Se = 37.4%, Sp = 85.7%).…”
Section: Discussionmentioning
confidence: 99%
“…This result shows that the scoring chart is also not a perfect measure to be used as a reference test for detecting respiratory disease. When applying scoring systems, the criteria for diagnosing respiratory diseases in different environments should also be taken into consideration [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…To estimate the Se and Sp of clinical scoring and thoracic ultrasound, a systematic literature review was conducted for the priors used in this analysis. In total, 4 papers were found that fulfilled the criteria for TUS (13,(23)(24)(25)) and 3 papers were found that fulfilled the criteria for CRS (23)(24)(25) (see Supplemental material for search strings, inclusion criteria and results). A mean Se for TUS was estimated at 0.73 (0.58, 0.86) and a mean Sp of 0.88 (0.83, 0.93) was estimated.…”
Section: Model Priors: Test Characteristicsmentioning
confidence: 99%
“…There are numerous published versions and interpretations of the Wisconsin respiratory scoring system (20,21,(26)(27)(28)(29), other scoring systems such as the California score also exist (22). The Se and Sp of clinical scoring varies widely in the literature (Se; 0.48-0.78, Sp; 0.74-0.99) (23)(24)(25). Clinical scoring systems can have poor inter-rater agreement as shown by Buckzinski et al (30).…”
mentioning
confidence: 99%
“…Pneumonias are a serious field problem of cattle significantly deters the level of productive and reproductive capacities of the herd and/or individual cases (Griffin et al, 1997 andDecaris et al, 2022). Bovine pneumonias are a multifactorial syndrome.…”
Section: Introductionmentioning
confidence: 99%